Analysis Trading International in Field Export Import in Indonesia - Ira Meilani Sipahutar; Meilany Dwi Syahfitri; Wira Hadi Sagura; Khairani Matondang; Riza Indrani (International Journal of Asian Business and Management, 2022)
Limited supplies in a country, import activities were initiated. Export-import activities as well can foster harmonious relations between nations. With this international trade, many party involved and you're welcome get profit, good profit results sell nor profit on fulfillment needs. Export import also is wrong one field work that has a big impact on business people. Prioritization of exports for Indonesia already been encouraged since 1983. The research method used is by applying normative or doctrinal legal research, with an analytical and comparative study approach law (comparative law) by emphasizing comparison with existing legal provisions regulate work agreements in several common law and civil law countries, as the basis of the foundation methodology study law. Amount activity export which increase will cause the demand for domestic currency increases and the exchange rate strengthens besides causing energy work absorbed in a manner full which means unemployment rate is reduced